The Making of the “Chinese Problem”: Indonesian Local Agencies’ Perceptions of Ethnic Chinese and Communist China, 1950-1979 - Didi Kwartanada (Universitas Gadjah Mada, 2020)
When Indonesia gained its independence, it knew almost nothing about its Chinese population of more than 2 million. During the Dutch colonial and Japanese occupation periods, the authorities established offices for Chinese Affairs staffed by sinologists; however, the young Republic of Indonesia did not have such experts. By the early 1950s, the Foreign Ministry set up its “School of Sinology”. The school’s founder was suspicious of Communist China and therefore viewed that Indonesia must be cautious, with the overseas Chinese in Indonesia constituting a “sumber subversi” (source of subversion). Its first class had twenty students and with the conduct of its first class can be regarded as the earliest effort to study China and the ethnic Chinese by the Indonesian authorities. In the turbulent 1950s and 1960s, the Chinese were considered a problem, and so the term “Chinese problem” (“Masalah Cina”) was created, which then became commonly used throughout the New Order period. This paper explores how perceptions about the Chinese and Communist China were shaped by local agencies during 1950-1979, who the agencies were, and their publications.. The paper looks at how scholars, journalists, intelligence bureau and publishing houses contributed to the construction of the perceived “Chinese Problem”. Particular focus is also given to sinology-trained military officer and their works, in shaping perceptions towards the Chinese in Indonesia and also mainland China.